Violence in William Golding’s and Flannery O’Connor’s Selected Works: a contrastive and comparative analysis - Samira Agnes de Cicco Sandes (2019)
Violence in works of literature is manifested in different manners, can have different levels, have different motivations and is experienced in different ways. The goal of this Master‘s dissertation is to analyze how violence is represented and its implications in selected works of Flannery O‘Connor and William Golding. On the one hand, in the case of Golding, the analysis consists mainly of how, in the novel Lord of the Flies, society plays a significant role when it comes to shaping human behavior in order to act or not act according to one‘s innate tendency to commit violent acts. To support this idea of violence being innate to all of us, Freud and his theory on how one is born violent and learns to live in society is used to corroborate the representation found in Lord of the Flies, together with the discussion and comparison of the concept of the ‗state of nature‘ found in the works of Locke, Rousseau and Hobbes. On the other hand, the main aspect explored in O‘Connor‘s short stories ―A Good Man is Hard to Find‖ and ―Revelation‖ is how violence is related to religion and to what some critics call ‗the moment of grace.‘ The moment of grace occurs when a character finally has an epiphany, accompanied by a violent act, about a specific aspect of their lives. This work aims at a closer view of the fictional representation of violence, focusing on how the social environment as well as one‘s beliefs affect one‘s attitudes toward it.